The Association between One Particular Green Building Program and the Use of Environmentally Certified Wood by US Homebuilders - Randall A. Cantrell; Indroneil Ganguly; Ivan Eastin; Tait Bowers (EDIS)
A recent survey of US homebuilders shows that there is an emerging trend for smaller- and medium-sized homebuilders to begin using the LEED for Homes green building program in the near future. Half of the homebuilders sampled desire to receive “green-building points,” and one way to do so is by using environmentally certified wood. LEED for Homes appears to have increased US homebuilder awareness of and use of environmentally certified wood. This 3-page fact sheet was written by Randall A. Cantrell, Indroneil Ganguly, Ivan Eastin, and Tait Bowers, and published by the UF Department of Family, Youth and Community Sciences, March 2012.